2019
DOI: 10.1590/1678-9865201932e180162
|View full text |Cite
|
Sign up to set email alerts
|

Nutritionist’s job market: 80 years of history

Abstract: Objective To analyze the increase in the number of nutritionists and the aspects of the job market in the last decade. Methods Critical test based on literature review and official data provided by nutrition councils and other entities. Results There was an average yearly increase of 8,248 nutritionists in the period from 2010 to 2017, having the largest contingent of professionals concentrated in the Brazilian Southeast region. In 2017 there were 126,539 nutritionists registered in the country’s ten regiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
4
0
2
Order By: Relevance
“…Among the main professional practice areas, Public Health had the smallest number of CHI. The number of nutritionists working in the National Health Service in Portugal and the Sistema Único de Saúde (SUS, Unified Health System) in Brazil is smaller than what is considered adequate and may have a relevant effect on the nutritionists' training [21][22][23]. The biologist approach, or "nutritionism", when food is understood as its nutrient profile at the expense of its social, human, and symbolic context, seems to prevail [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the main professional practice areas, Public Health had the smallest number of CHI. The number of nutritionists working in the National Health Service in Portugal and the Sistema Único de Saúde (SUS, Unified Health System) in Brazil is smaller than what is considered adequate and may have a relevant effect on the nutritionists' training [21][22][23]. The biologist approach, or "nutritionism", when food is understood as its nutrient profile at the expense of its social, human, and symbolic context, seems to prevail [24].…”
Section: Discussionmentioning
confidence: 99%
“…The studied Brazilian HEI showed higher CHI rates for the FNE, Human and Social Sciences, and Professional within social and human sciences axis. This is probably influenced by the several pedagogical reformulations that took place since the establishment of the first nutrition undergraduate program in 1939, which in turn were fostered by discussions about the role of nutritionists in ensuring food and nutrition security [13,18,23]. Brazil has profound inequalities due to its colonial history and land size and is marked by the prevalence of hunger and a rapid increase in obesity rates, both results of food insecurity.…”
Section: Discussionmentioning
confidence: 99%
“…In the thematic of Collective Health, we found that only 13.0% of the works were aimed at studying public nutrition policies and that only 1.9% of the FPs focused on public health policies. On the other hand, according to Gabriel et al (2019), nutrition has been consolidated, above all, through the implementation of public policies and programs that include nutritionists in their scope, with numerous advances in recent years that have influenced the fields of work and professional activity.…”
Section: Discussionmentioning
confidence: 99%
“…Houve um crescente aumento do número de profissionais nutricionistas formados, concomitante com a ampliação e diversificação do mercado de trabalho, indicando a necessidade do avanço nas áreas de atuação, com uma visão mais ampla da profissão (GABRIEL et al, 2019). Neste sentido, o objetivo deste artigo é relatar a experiência na disciplina de Estágio Curricular Obrigatório de Ciências dos Alimentos dos cursos de Nutrição da Universidade Federal de Mato Grosso do Sul (UFMS), em Campo Grande, MS, e da Universidade Federal da Grande Dourados (UFGD), em Dourados, MS.…”
Section: Introductionunclassified